Profiling youth participation in volunteer activities in Malaysia: understanding the motivational factors influencing participation in volunteer work among Malaysian youth - Abdullah Sahimi, Nur Aishah Hamizah; Suandi, Turiman; Ismail, Ismi Arif; Hamzah, Siti Raba'ah (Universiti Putra Malaysia Press, 2018)
The involvement of youth in volunteer work is essential as it enables them to contribute to society (Checkoway, 2011). However, profile studies on Malaysian youth participation in volunteer activities are scarce and the subject warrants further research (Siti Raba'ah et al., 2011; Turiman et al., 2009). What is the level of participation of youth in volunteer activities? What hinders or motivates them to participate in volunteering work? This research profiles youth participation in volunteer activities in Malaysia. Specifically, it is aimed at profiling: 1) factors that motivate youth to participate in volunteer work; 2) the level of motivation towards participation in volunteer work among Malaysian youth; and 3) the most dominant motivation factor of youth participation in volunteer work. A total of 342 Malaysian youths participated in this nationwide study. A Youth Motivation on Participation in Volunteering Questionnaire was administered to Malaysian youth. Data were analysed and interpreted to provide the key findings on Malaysian youth engagement and participation in volunteer work. This study shows that the relationship between motivation and participation in volunteer work is positively significant. It shows that almost all the respondents in this study participating in voluntary activities were influenced by a number of motivating factors. The study ends with recommendations for policy makers and practitioners on how to attract youth to participate and to engage more effectively in volunteer work.